Implementasi Perjanjian Kredit Perbankan Dalam Mewujudkan Kepatuhan Debitur dan Efektivitas Perjanjian - Alvian, Muhammad Adzel; Agustini, Shenti; Fitri, Winda (Universitas Medan Area, 2024)
Banking Credit is an agreement between a bank (creditor) and a borrower (debtor) that regulates the provision of loans by banks to customers. This agreement includes various terms and conditions that must be met by both parties, including the loan amount, interest rate, payment period, installment payment obligations, and the rights and obligations of each party. Examples of provisions often found in this agreement are the debtor's obligation to pay installments on time, provisions regarding late fees, and conditions governing the use of collateral in the form of assets that can be auctioned if the debtor fails to pay the debt. This research aims to discuss the rules related to banking credit agreements and the implementation of banking credit agreements, especially by banks, so that these agreements can be obeyed by debtors and run effectively. The method used in this research is the Empirical research method which uses data collection techniques through interviews. credit agreements use standard contracts that contain the rights and obligations of both parties. To mitigate the risk of default, collateral is required and can be sold if the debtor fails to pay. The principle of prudence is applied so that banks remain healthy and maintain public trust. An effective credit agreement involves analyzing the prospective debtor's eligibility, drafting a clear agreement, and monitoring the debtor's performance on an ongoing basis.Banking Credit Agreement is an agreement between a bank (creditor) and a borrower (debtor) that regulates the provision of loans by banks to customers. This agreement includes various terms and conditions that must be met by both parties, including the amount of the loan, the interest rate, the payment period, and the obligations and rights of each party. the purpose of this study is to discuss the rules related to banking credit agreements and the implementation of banking credit agreements, especially the bank so that the agreement can be obeyed by the debtor and run effectively. the method used in this study is empirical, the credit agreement uses a standard contractthath contains the rights and obligationof both parties. To mitigate the risk of defaul, collateral is required and can be sold if the debtor fails to pay. The percautionary principle is applied so that banks remain healthy, As well as maintaining public trust. an effective credit agreement involves analyzing the eligibility of the prospective debtor, drafting a clear agreement, and monitoring the debtor's performance on an ongoing basis to minimze risks and ensure debtor compliance